Fentanyl and Driving Impairment. Issue 4 (14th August 2020) - Rohrig, Timothy P; Nash, Emily; Osawa, Kei A; Shan, Xiaoqin; Scarneo, Colleen; Youso, Kimberly B; Miller, Russell; Tiscione, Nicholas B
Abstract: The incidence of fentanyl in forensic toxicology analyses in the USA has dramatically increased over the past several years. The increase in death cases has been well studied; however, little has been reported on the impact to drug impaired driving. Fentanyl driving while under the influence of drugs (DUID) case data from 2014 to 2019 is presented. The data were obtained from three toxicology laboratories in the Northeast, Southeast, and Midwest regions of the USA. Fentanyl whole blood concentrations ranged from 0.1 to 157 ng/mL in living drivers with a 466% to 524% increase in fentanyl-positive DUID cases from 2014 to 2019, depending on the US region. The vast majority of fentanyl cases involved poly-drug use. Twenty case histories are presented where fentanyl was the only drug identified. The mean (standard deviation) fentanyl concentration for these cases was 5.2 ± 3.8 ng/mL with a median of 3.7 ng/mL, and the concentrations ranged from 2.0 to 16 ng/mL. Naloxone administration was documented in exactly half of these cases similar to another study involving carfentanil-impaired driving. The case histories also demonstrate that some recreational opioid users may display limited signs of impairment either due to tolerance or naloxone administration. The top three observations in common among the cases were the driver was found unresponsive behind the wheel, the vehicle left the travel lane or roadway, and the driver was involved in a crash. The increase in fentanyl use not only poses a risk for overdose and death, but is also a significant concern for traffic safety. This study supports the movement of fentanyl from a Tier II drug to Tier I due to its significant potential for impairment and increase in prevalence in impaired driving cases.